Recent theoretical developments in quarkonia production in relativistic heavy ion collisions - Zhao Jiaxing (EPJ Web of Conferences)
Quarkonia are golden probes of heavy ion collisions that have attracted much attention from both experimental and theoretical perspectives. This paper will review recent theoretical studies on quarkonium thermal properties, with a particular focus on the heavy quark finite-temperature potential obtained by Lattice QCD and other approaches. Moreover, it will examine the advancements in the real-time evolution of quarkonia in heavy ion collisions.